Infection Control Measures in Private Dental Clinics in Lebanon. (31st May 2017) - Dagher, Jihad; Sfeir, Charles; Abdallah, Ahmad; Majzoub, Zeina
Abstract : Purpose . Evaluate infection control knowledge, attitude, and practice in Lebanese private dental clinics. Materials and Methods . A survey including 46 questions related to routine safety procedures was sent to 1150 Lebanese dentists between July 1st and 2nd, 2015. The study sample was selected from the database of registered dentists based on a proportional random sampling ensuring equitable representation of the 5 geographic regions of Lebanon. A subset of 29 questions was used to generate an overall score of compliance (excellent, good, fair, and poor). Comparisons according to gender, type, region, and years of practice were performed. Results . 417 dentists returned the completed questionnaires. 96% expressed concern about infection transmission, 90.6% were vaccinated against Hepatitis B, and 61.8% asked routinely about patients medical history. Only 43% used protective eyewear. Although most dentists (65%) used autoclaves, dry heat was still used. Significant correlations were found between gender and use of personal protective equipment. Less compliance was shown by clinicians with fewer years of experience. In the overall compliance questionnaire, the mean percentage of correct answers was roughly 54% with <5% of the practitioners scoring "excellent." Conclusions . The study found inadequacy of compliance in private Lebanese dental clinics necessitating improved educational training and sustained monitoring by regulatory bodies.